2006
DOI: 10.1253/circj.70.691
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 16-Slice Multislice Spiral Computed Tomography for Follow-up Study of Coronary Stent Implantation

Abstract: n recent years, coronary stent implantation has become an established method for treating patients with coronary artery disease. However, in-stent restenosis attributable to intimal hyperplasia still occurs at a relatively high rate, not only with bare metal stents but also with drug eluting stents. 1,2 Conventional coronary angiography is still the domain of the assessment of 'in-stent' restenosis. However, angiography has limitations because of its invasiveness and high medical expense. Thus, a non-invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The 16-slice CT scanners are more successful than 4-slice CT scanners in evaluation of intracoronary stents with high imaging quality due to thinner slices, high gantry rotation speed and short breath-hold period. The sensitivity and specificity of 16-slice CT scanners in detection of intracoronary stent restenosis ranged between 57-83% and 88-99%, respectively and the average rate of assessed stents was 86% (Schuijf et al, 2004;Gilardi et al, 2006;Kitagawa et al, 2006, Watanabe et al, 2006Kefer et al, 2007;Soon et al, 2007). In our study, the sensitivity of 33% is quite low compared to other studies, but the specificity is compatible with other studies.…”
Section: Discussionsupporting
confidence: 85%
“…The 16-slice CT scanners are more successful than 4-slice CT scanners in evaluation of intracoronary stents with high imaging quality due to thinner slices, high gantry rotation speed and short breath-hold period. The sensitivity and specificity of 16-slice CT scanners in detection of intracoronary stent restenosis ranged between 57-83% and 88-99%, respectively and the average rate of assessed stents was 86% (Schuijf et al, 2004;Gilardi et al, 2006;Kitagawa et al, 2006, Watanabe et al, 2006Kefer et al, 2007;Soon et al, 2007). In our study, the sensitivity of 33% is quite low compared to other studies, but the specificity is compatible with other studies.…”
Section: Discussionsupporting
confidence: 85%
“…It has been suggested that MSCT could reduce the need for invasive diagnostic procedures by non-invasively excluding in-stent restenosis [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The present meta-analysis identifies that this optimistic view could be envisioned only in highly selected patients and mainly in patients with proximal and large stents, as frequently commented on in the individual studies [22,23].…”
Section: Discussionmentioning
confidence: 56%
“…The present meta-analysis identifies that this optimistic view could be envisioned only in highly selected patients and mainly in patients with proximal and large stents, as frequently commented on in the individual studies [22,23]. Indeed small stent diameter has been identified by several groups as a major factor for failure of in-stent restenosis assessment, with a consensus that only stents with diameter >3 mm are routinely interpretable [6,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. However, in routine clinical settings, many patients are treated with relatively small stents, having diameters of 2.5 mm or 3.0 mm.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…5). Newer scanners with progressively greater fields of view have now been applied in patients with various types of stents [74,75,76,77,78,79,80,81,82,83]. For example, using a 40-slice scanner, our group has shown that the extent of luminal stent diameter obscured due to the blooming artifact averages about one third of the luminal diameter of the stent [84].…”
Section: Assessment After Revascularizationmentioning
confidence: 99%